2010
DOI: 10.1002/ijc.25680
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Hodgkin lymphoma and autoimmunity: Does gender matter?

Abstract: Autoimmune disorders are more frequent in women, whereas most non-Hodgkin lymphomas (NHLs) are common in men; yet, sexspecific autoimmune-lymphoma associations are rarely reported. Detailed data on autoimmune disease were abstracted from medical records of 791 cases (including 316 diffuse large B-cell lymphomas (DLBCLs); 228 follicular lymphomas (FLs); 127 marginal zone lymphomas (MZLs); 64 T-cell lymphomas and 38 mantle cell lymphomas) and 872 controls. The combined prevalence of autoimmune disease was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 33 publications
3
43
1
Order By: Relevance
“…This reflects the known association between gluten-sensitive enteropathy and EATCL, for which risks as varied as 6-to over 200-fold have been reported [5,7,8,11,34]. Similarly, risks for T-cell lymphoma as a whole ranged from 6-to over 50-fold [3,8,18,31,32,36]. Diffuse large B-cell [11-17, 19-22, 24, 26, 28, 30, 33, 34]; observed cases of non-Hodgkin lymphoma and total number of 100,000 person-years (P-Yrs) among persons with (Exp) and without (Unexp) gluten-sensitive enteropathy in nested case-control studies [4,18,27,29,35]; or the number of nonHodgkin lymphoma cases and controls who did (Exp) and did not (Unexp) have gluten-sensitive enteropathy in case-control studies [6-10, 23, 25, 31, 32, 36].…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…This reflects the known association between gluten-sensitive enteropathy and EATCL, for which risks as varied as 6-to over 200-fold have been reported [5,7,8,11,34]. Similarly, risks for T-cell lymphoma as a whole ranged from 6-to over 50-fold [3,8,18,31,32,36]. Diffuse large B-cell [11-17, 19-22, 24, 26, 28, 30, 33, 34]; observed cases of non-Hodgkin lymphoma and total number of 100,000 person-years (P-Yrs) among persons with (Exp) and without (Unexp) gluten-sensitive enteropathy in nested case-control studies [4,18,27,29,35]; or the number of nonHodgkin lymphoma cases and controls who did (Exp) and did not (Unexp) have gluten-sensitive enteropathy in case-control studies [6-10, 23, 25, 31, 32, 36].…”
Section: Resultsmentioning
confidence: 79%
“…Among the homogeneous studies, five reported risks by sex [23,25,26,31,32]. Women with gluten-sensitive enteropathy were found to have similar risks of NHL to men (pooled risk estimate = 4.87, 95% CI 2.96-8.02, I 2 = 4%, p(heterogeneity) = 0.39; pooled risk estimate = 4.43, 95% CI 2.91-6.74, I 2 = 0%, p(heterogeneity) = 0.98, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations